Battery, battery pack, and electric device
Patent Information
- Application Number
- CN202510573371.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
从电池设计角度,正极片包括含锂层状金属氧化物,负极片包含天然石墨,将两者结合组成的电池可以贡献更高的能量密度,但是层状结构的活性材料在锂离子充放电过程中的容易膨胀,导致的结构不稳定,会影响电池的循环寿命
[0025]本申请提供的电池包含负极片和正极片,负极片满足K为6~18,其中K通过包含天然石墨的负极片的晶体学参数、天然石墨的孔隙密度以及负极片的压实密度关系计算得到,正极片包括含锂层状金属氧化物;当负极片满足K时,一方面,对负极片的内部孔隙、负极片的综合微晶尺寸以及负极片压实密度的综合调控,可有效降提升电池的循环寿命;在另一方面,正极片包括含锂层状金属氧化物,与负极片中的天然石墨同属层状嵌锂材料,当锂离子在正负极之间嵌入/脱出时,两者交替膨胀,可有效降低负极片在嵌锂过程中的体积膨胀,得到长循环性能与高能量密度的电池。
Smart Images

Figure BDA0005388938760000141 
Figure BDA0005388938760000151 
Figure BDA0005388938760000152
Abstract
Description
Technical Field
[0001] This application relates to a battery, and more particularly to a battery, battery pack, and electrical device, belonging to the field of battery technology. Background Technology
[0002] With the widespread application of batteries in electronic devices, passenger vehicles, and energy storage facilities, consumers are placing higher demands on the energy density and lifespan of these energy storage carriers. From an environmental perspective, as global attention to carbon footprint increases, artificial graphite, which consumes a significant amount of energy during its production, faces increasingly stringent environmental requirements. From a battery design perspective, a battery combining a lithium-containing layered metal oxide cathode and natural graphite anode can contribute higher energy density. However, the layered structure of the active material is prone to expansion during lithium-ion charging and discharging, leading to structural instability and affecting the battery's cycle life.
[0003] Therefore, it is necessary to optimize the design of batteries to give them both good cycle life and high energy density. Summary of the Invention
[0004] This application provides a battery that has long cycle performance and high energy density.
[0005] This application also provides a battery pack comprising a plurality of the aforementioned batteries, which has long cycle performance and high energy density characteristics.
[0006] This application also provides an electrical device that includes the aforementioned battery or battery pack.
[0007] This application provides a battery, including a negative electrode and a positive electrode, wherein the negative electrode and the positive electrode are stacked; the negative electrode includes a negative current collector and a negative active material layer disposed on at least one side surface of the negative current collector, the negative active material layer includes a negative active material, the negative active material includes a carbon-based material, the carbon-based material includes natural graphite, and the negative electrode satisfies K, where K is 6 to 18;
[0008] Wherein, K is calculated using Equation 1: K = (C 101 +C 002 )×PDa×ρ P Formula 1;
[0009] In Equation 1, C 101 and C 002 The crystallographic parameters of the carbon-based material are calculated using Equations 2 and 3, respectively, with units of nm; PDa is the compaction density of the negative electrode sheet, with units of g / cm³. 3 ;ρ PThe pore density of the natural graphite in the negative electrode sheet is expressed in mL / g.
[0010] C 101 =1.84×λ / (FWHM) 101 ×cosθ 101 Formula 2;
[0011] C 002 =0.89×λ / (FWHM) 002 ×cosθ 002 Formula 3;
[0012] In Equations 2 and 3, FWHM 101 and FWHM 002 θ represents the half-width at half-maximum (FWHM) of peaks (101) and (002) in the X-ray diffraction pattern of the negative electrode, respectively, in radians; 101 and θ 002 λ represents half the 2θ values of the (101) peak and (002) peak in the X-ray diffraction pattern of the negative electrode, respectively, both in °; λ is the wavelength of the cathode ray used in X-ray diffraction, in nm.
[0013] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side surface of the positive current collector. The positive active material layer includes a positive active material, which includes a lithium-containing layered metal oxide.
[0014] The battery as described above, wherein C 101 +C 002 The wavelength range is 70nm to 120nm.
[0015] The battery as described above, wherein ρ P The concentration is 0.05–0.09 mL / g.
[0016] In the battery described above, the PDa is 1.6–1.85 g / cm³. 3 .
[0017] In the battery described above, the mass content of the natural graphite is 50% to 100% based on the total mass of the negative electrode active material.
[0018] In the battery described above, the Dv50 of the natural graphite is 12μm to 18μm.
[0019] The battery as described above, wherein the lithium-containing layered metal oxide includes one or more combinations of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, and nickel-cobalt-aluminum ternary materials.
[0020] In the battery described above, the compaction density PDc of the positive electrode is 3.2–3.6 g / cm³. 3 .
[0021] In the battery described above, the mass content of the lithium-containing layered metal oxide is 60% to 98% based on the total mass of the positive electrode active material.
[0022] In the battery described above, the Dv50 of the lithium-containing layered metal oxide is 5 μm to 12 μm.
[0023] A second aspect of this application provides a battery pack including a plurality of batteries connected in series, parallel, or mixed connections, wherein the batteries include the batteries provided in the first aspect of this application.
[0024] A third aspect of this application provides an electrical device, including the battery provided in the first aspect of this application or the battery pack provided in the second aspect of this application.
[0025] The battery provided in this application includes a negative electrode and a positive electrode. The negative electrode satisfies K as 6 to 18, where K is calculated by the relationship between the crystallographic parameters of the negative electrode containing natural graphite, the pore density of natural graphite, and the compaction density of the negative electrode. The positive electrode includes a lithium-containing layered metal oxide. When the negative electrode satisfies K, on the one hand, the comprehensive control of the internal pores, the overall crystallite size, and the compaction density of the negative electrode can effectively improve the cycle life of the battery. On the other hand, the positive electrode includes a lithium-containing layered metal oxide, which, like the natural graphite in the negative electrode, belongs to the layered lithium intercalation material. When lithium ions are inserted / extracted between the positive and negative electrodes, the two expand alternately, which can effectively reduce the volume expansion of the negative electrode during the lithium intercalation process, resulting in a battery with long cycle performance and high energy density. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0027] With the widespread application of batteries in electronic devices, passenger vehicles, and energy storage facilities, consumers are placing higher demands on the energy density and lifespan of these energy storage carriers. From an environmental perspective, as global attention to carbon footprint increases, artificial graphite, which consumes a significant amount of energy during its production, faces increasingly stringent environmental requirements. From a battery design perspective, a battery combining a positive electrode containing lithium-containing layered metal oxides and a negative electrode containing natural graphite can contribute higher energy density. However, the expansion and contraction of the layered active material during lithium-ion charging and discharging leads to structural instability, which can affect the battery's cycle life.
[0028] Based on this, this application provides a battery, including a negative electrode and a positive electrode, wherein the negative electrode and the positive electrode are stacked; the negative electrode includes a negative current collector and a negative active material layer disposed on at least one side surface of the negative current collector, the negative active material layer includes a negative active material, the negative active material includes a carbon-based material, the carbon-based material includes natural graphite, and the negative electrode satisfies K, where K is 6 to 18;
[0029] Wherein, K is calculated using Equation 1: K = (C 101 +C 002 )×PDa×ρ P Formula 1;
[0030] In Equation 1, C 101 and C 002 The crystallographic parameters of the carbon-based material are calculated using Equations 2 and 3, respectively, with units of nm; PDa is the compaction density of the negative electrode sheet, with units of g / cm³. 3 ;ρ P The pore density of the natural graphite in the negative electrode sheet is expressed in mL / g.
[0031] C 101 =1.84×λ / (FWHM) 101 ×cosθ 101 Formula 2;
[0032] C 002 =0.89×λ / (FWHM) 002 ×cosθ 002 Formula 3;
[0033] In Equations 2 and 3, FWHM 101 and FWHM 002 θ represents the half-width at half-maximum (FWHM) of peaks (101) and (002) in the X-ray diffraction pattern of the negative electrode, respectively, in radians; 101 and θ 002λ represents half the 2θ values of the (101) peak and (002) peak in the X-ray diffraction pattern of the negative electrode, respectively, both in °; λ is the wavelength of the cathode ray used in X-ray diffraction, in nm.
[0034] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side surface of the positive current collector. The positive active material layer includes a positive active material, which includes a lithium-containing layered metal oxide.
[0035] For example, when FWHM 101 When the value is 0.3°, the value can be converted to radians as follows: 0.3 × π / 180 = 0.005233.
[0036] For example, the value of K includes, but is not limited to, a range of 6, 7.17, 8.13, 9.12, 10, 11, 12.21, 13, 14, 15.26, 16, 17, 18, or any two of these.
[0037] Among them, the (101) peak and (002) peak in the X-ray diffraction pattern of the negative electrode are derived from the carbon-based materials contained in the negative electrode, especially natural graphite.
[0038] In detail, λ is the wavelength of the cathode ray used in X-ray diffraction, which is determined by the cathode material (i.e., target material) of the X-ray tube and the operating conditions of the X-ray tube. In one specific embodiment, the wavelength of the cathode ray used in X-ray diffraction (copper target Kα) is λ, which is 0.15418 nm.
[0039] The half-peak width (WHM) of the (101) and (002) peaks in the X-ray diffraction pattern of the negative electrode refers to the peak width at half the peak height of the (101) and (002) peaks. It should be noted that the (101) and (002) peaks in the X-ray diffraction pattern of this application refer to the (101) and (002) peaks of all types of carbon in the negative electrode, including carbon materials existing in the form of negative electrode active materials and carbon materials existing in the form of conductive agents.
[0040] In X-ray diffraction patterns, the full width at half maximum (FWHM) can be used to estimate the average grain size, crystal defects, and phase characteristics of carbon-based materials, especially natural graphite, in negative electrodes.
[0041] The porosity of natural graphite in a negative electrode refers to the volume of natural graphite pores within a unit mass of the negative electrode active material layer, which can be tested using mercury intrusion porosimetry. In this application, the porosity of natural graphite is determined as follows: the negative electrode is tested using a mercury intrusion porosimetry instrument. The test is based on the Washburn equation, r = -2σcosθ / P, where r is the pore diameter of an ideal cylindrical inner hole, σ is the surface tension of mercury, θ is the contact angle of mercury, and P is the mercury intrusion pressure. Under certain test conditions, the surface tension of mercury and its contact angle remain constant. The larger the pore diameter of the sample (negative electrode), the smaller the capillary resistance and the smaller the mercury intrusion pressure. Therefore, as the mercury intrusion pressure increases, mercury will gradually intrude from the larger pores into the smaller pores. By testing the negative electrode using the mercury intrusion porosimetry method and converting the results according to the Washburn equation, the relationship curve between pore diameter and mercury intrusion amount, as well as the pore diameter distribution curve, can be obtained. In summary, the porosity of natural graphite in the negative electrode of this application is obtained by integrating the pore size distribution curve of the negative electrode obtained by mercury intrusion porosimetry and taking pore sizes from 5 nm to 500 nm.
[0042] The compaction density of a negative electrode refers to its bulk density under a certain pressure. The compaction density of the negative electrode in this application is determined as follows.
[0043] Method for testing the compaction density of the negative electrode sheet: 1) Disassemble the battery after complete discharge to obtain the negative electrode sheet; immerse the negative electrode sheet in dimethyl carbonate (DMC) solvent for 10-20 minutes to clean off residual electrolyte, and then dry the negative electrode sheet; 2) Take the above negative electrode sheet and cut out small circular pieces of a certain diameter. Scrape off the coating layer on one side of the small circular piece with a ceramic scraper (or polish it off with sandpaper), and obtain the total weight of the coating on one side of the small circular piece. Calculate the weight of the coating on one side of the small circular piece per unit area, which is the single-sided areal density of the negative electrode active material layer. Calculate the compaction density of the negative electrode sheet by dividing the single-sided areal density of the negative electrode sheet by the thickness of the single-sided negative electrode active material layer.
[0044] The negative electrode sheet requires a certain rolling and shaping process during its preparation. However, the existing rolling and shaping process has little effect on optimizing the crystal structure and internal pores of natural graphite, resulting in a large expansion rate of the negative electrode sheet and a large consumption of electrolyte and active ions, which in turn leads to poor cycle performance and energy density of the battery.
[0045] When the negative electrode sheet provided in this application has a K value of 6 to 18, the battery exhibits long cycle performance and high energy density characteristics when used in a battery.
[0046] After extensive experimentation and analysis of the results, the inventors preliminarily concluded that the reasons for the poor performance are as follows: the energy density and lifespan characteristics of the negative electrode are mainly affected by the crystallographic parameters of the negative electrode containing natural graphite, the internal porosity of the natural graphite, and the compaction density of the negative electrode. Regarding crystallographic parameters, on the one hand, the ordered structural size (i.e., crystallographic parameters) of the carbon-based material including natural graphite determines the specific capacity of the negative electrode active material. A higher ordered lattice size means a higher proportion of natural graphite in the carbon-based material can form LiC6 layered compounds. Furthermore, the larger the ordered lattice size, the lower the modulus of the carbon-based material including natural graphite, the stronger its compaction ability, and the higher the energy density of the battery. On the other hand, as the size of the crystallographic parameters increases, the size of the expandable units in the carbon-based material including natural graphite increases, leading to greater volume expansion during charge and discharge, and a decrease in cycle stability. The internal pores of natural graphite come into contact with the electrolyte, consuming active lithium ions and affecting the battery's cycle stability. Increasing the compaction density of the negative electrode will improve the volumetric energy density of the battery, but excessively high compaction density will cause volume expansion and particle rearrangement of the negative electrode during cycling, which is detrimental to the battery's lifespan performance.
[0047] Based on the above reasons, this application comprehensively analyzes the main parameters of the negative electrode that affect the battery's energy density and lifespan performance, and obtains the following relationship: K = (C 101 +C 002 )×PDa×ρ P Furthermore, the inventors discovered that when the aforementioned negative electrode is combined with a positive electrode containing lithium-containing layered metal oxides, the expansion rate of the negative electrode is reduced, and the battery exhibits long cycle performance and high energy density characteristics.
[0048] Furthermore, in one specific embodiment of this application, C 101 +C 002 The wavelength range is 70nm to 120nm.
[0049] In detail, C 101 +C 002 Including but not limited to 70nm, 82nm, 85nm, 90nm, 99nm, 100nm, 105nm, 110nm, 120nm, or any combination thereof.
[0050] Crystallographic parameters determine the size of the expandable crystal units after active ions intercalate into carbon-based materials, including natural graphite, to form layered compounds, further affecting the expansion ratio of the negative electrode. As crystallographic parameters increase, the true density increases, and the size and proportion of the ordered structure in carbon-based materials, including natural graphite, increase. This leads to a higher volume expansion ratio during lithium intercalation, resulting in faster SEI film rupture and repair during repeated charge-discharge cycles, accelerating the cycle consumption rate. On the other hand, the size of the ordered structure determines the reversible capacity of carbon-based materials, including natural graphite, through the formation of layered compounds, thus affecting the material's energy density. Experimental verification shows that crystallographic parameters in the range of 70nm–120nm can not only reduce the reversible expansion ratio of the negative electrode but also maintain the battery's energy density.
[0051] Furthermore, in one specific embodiment of this application, the porosity ρ of the natural graphite in the negative electrode sheet is... P The concentration is 0.05–0.09 mL / g.
[0052] In detail, ρ P This includes, but is not limited to, ranges of 0.05 mL / g, 0.053 mL / g, 0.058 mL / g, 0.06 mL / g, 0.061 mL / g, 0.069 mL / g, 0.07 mL / g, 0.075 mL / g, 0.079 mL / g, 0.08 mL / g, 0.085 mL / g, 0.09 mL / g, or any combination thereof.
[0053] When the porosity of natural graphite in the negative electrode is within the above range, it can further increase the lithium-ion storage capacity, provide a richer charge transport path, promote lithium-ion diffusion, and alleviate the side reactions between the negative electrode and the electrolyte, thereby enabling the battery to have high energy density and long cycle life.
[0054] In one specific embodiment of this application, PDa is 1.6–1.85 g / cm³. 3 .
[0055] Specifically, the compaction density (PDa) of the negative electrode sheet includes, but is not limited to, 1.6 g / cm³. 3 1.65g / cm 3 1.7g / cm 3 1.72g / cm 3 1.75g / cm 3 1.77g / cm 3 1.79g / cm 3 1.8g / cm 3 1.82g / cm 3 1.85g / cm 3Or a range consisting of any two of them.
[0056] When the compaction density of the negative electrode is within the above range, it helps to further balance the energy density of the battery, especially the volumetric energy density.
[0057] In one specific embodiment of this application, the mass content of natural graphite is 50% to 100% based on the total mass of the negative electrode active material.
[0058] Specifically, based on the total mass of the negative electrode active material, the mass content of natural graphite includes, but is not limited to, a range of 50%, 60%, 70%, 80%, 90%, 100%, or any combination thereof. By controlling the content of natural graphite within the above range, the performance of the negative electrode sheet can be better regulated based on the relationship defined in this application, and the higher the content of natural graphite, the more precise the regulation.
[0059] Wherein, based on the total mass of the negative electrode active material, when the mass content of natural graphite is less than 100%, the negative electrode sheet also includes other types of negative electrode active materials. This application does not limit the specific type of other types of negative electrode active materials, and can select at least one of the negative electrode active materials commonly used in the field, such as artificial graphite (including graphite materials processed from raw materials such as petroleum coke, needle coke, and isotropic coke), hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon suboxide and silicon-carbon negative electrodes), and tin-based negative electrode materials (mainly including tin and tin alloys).
[0060] Furthermore, in one specific embodiment of this application, the Dv50 of natural graphite is 12μm to 18μm. A Dv50 within this range is beneficial for compacting the internal voids of the natural graphite during negative electrode rolling, thereby increasing the cycle performance of the battery.
[0061] In this application, "Dv50" refers to the particle size corresponding to a cumulative volume percentage of 50%.
[0062] The method for testing the particle size D50 of natural graphite is as follows: using SEM images at 5000x magnification, the longest diameter of approximately 300 individual graphite particles is statistically analyzed, and the data distribution is calculated to determine the particle size D50 of natural graphite. The SEM images can be obtained by scanning the surface of the negative electrode or by scanning the cross-section of the negative electrode; this invention application does not impose any limitation on the method.
[0063] Furthermore, in one specific embodiment of this application, the thickness of the negative electrode sheet is 150 μm to 200 μm. A negative electrode sheet with a thickness within this range results in a more efficient battery.
[0064] For example, the thickness of the negative electrode sheet includes, but is not limited to, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm, 180 μm, 185 μm, 190 μm, 195 μm, 200 μm, or any combination thereof.
[0065] In one specific embodiment of this application, the lithium-containing layered metal oxide includes one or more combinations of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, and nickel-cobalt-aluminum ternary materials.
[0066] The aforementioned positive electrode material can provide higher energy density and is compatible with the negative electrode sheet provided in this application.
[0067] Furthermore, in one specific embodiment of this application, the Dv50 of the lithium-containing layered metal oxide is 5 μm to 12 μm. A Dv50 within this range is advantageous for compatibility with the negative electrode.
[0068] For example, the Dv50 of lithium-containing layered metal oxides includes, but is not limited to, a range of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or any combination thereof.
[0069] The method for testing the particle size D50 of lithium-containing layered metal oxides is as follows: using SEM images at 5000x magnification, the maximum diameter of approximately 300 positive electrode active materials is statistically analyzed, and the data distribution is calculated to determine the particle size D50 of the positive electrode active material. The SEM images can be obtained by scanning the surface of the positive electrode sheet or by scanning the cross-section of the positive electrode sheet; this invention application does not impose any limitation on this method.
[0070] Furthermore, in one specific embodiment of this application, the thickness of the positive electrode sheet is 160μm to 240μm. When the positive electrode sheet with the above thickness range is assembled into a battery with the negative electrode sheet of this application, the electrode thickness is highly compatible, which is beneficial to balancing the diffusion resistance of lithium ions in the positive and negative electrodes and increasing battery performance.
[0071] For example, the thickness of the positive electrode sheet includes, but is not limited to, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm or any combination thereof.
[0072] In this application, the thickness of the positive electrode or negative electrode refers to the total thickness of the active material layer (positive electrode corresponds to the positive active material layer, negative electrode corresponds to the negative active material layer) and the current collector (positive electrode corresponds to the positive current collector, negative electrode corresponds to the negative current collector).
[0073] In one specific embodiment of this application, the compaction density PDc of the positive electrode is 3.2–3.6 g / cm³. 3 When positive electrode sheets with the above-mentioned compaction density range are assembled into batteries with the negative electrode sheets of this application, the battery compatibility is high, which is beneficial to balancing the diffusion resistance of lithium ions in the positive and negative electrode sheets and increasing battery performance.
[0074] For example, the compaction density of the positive electrode sheet includes, but is not limited to, 3.2 g / cm³. 3 3.3g / cm 3 3.4g / cm 3 3.5g / cm 3 3.6g / cm 3 Or the range formed by any two of them.
[0075] In one specific embodiment of this application, the mass content of the lithium-containing layered metal oxide is 60% to 98% based on the total mass of the positive electrode active material. When the positive electrode sheet with the above-mentioned lithium-containing layered metal oxide content is assembled into a battery with the negative electrode sheet of this application, the battery has high compatibility, which is beneficial to increasing battery performance.
[0076] For example, the mass content of the lithium-containing layered metal oxide is 60%, 65%, 70%, 74%, 79%, 83%, 87%, 92%, 95%, 98%, or any combination thereof.
[0077] It is conceivable that, in addition to the aforementioned negative electrode and positive electrode, the battery of the present invention also includes an electrolyte and a separator.
[0078] This application does not strictly limit the choice of electrolyte, which may include one or more solvents commonly used in current battery electrolytes, as well as lithium salts commonly used in current electrolytes. For example, the solvent may include at least one of ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, and γ-butyrolactone; the lithium salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0079] This application does not strictly limit the choice of separator material. It can be one of the separator materials commonly used in batteries, such as polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polyimide electrospun separator (PI), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), cellulose nonwoven separator, and separator with ceramic coating.
[0080] In the preparation of lithium-ion batteries, the positive electrode, separator, and negative electrode are wound or stacked to obtain bare cells, which are then packed into pre-stamped aluminum-plastic film bags or battery casings. After the packed batteries are dried at 85°C, electrolyte is injected into the dried batteries. After the batteries are left to stand, formed, and sealed, the preparation of the lithium-ion battery is completed.
[0081] The method for preparing the negative electrode sheet according to the first aspect of this application includes the following steps:
[0082] 1) A layer of negative electrode active material is disposed on at least one side surface of the negative electrode current collector;
[0083] 2) Roll pressing is performed on the negative electrode active material layer to obtain a negative electrode sheet; the rolling temperature is 130℃~170℃; and / or the rolling pressure is 115MPa~170MPa; and / or the belt speed is 6m / min~9m / min.
[0084] The preparation method provided in this application adopts a hot rolling process. By controlling the temperature, pressure and rolling speed of the hot rolling process, the internal pores of the natural graphite material in the negative electrode and the lattice parameters of the carbon-based material in the negative electrode are optimized to obtain a negative electrode that meets the requirements of this scheme, thereby enabling the battery to have both long cycle performance and high energy density characteristics.
[0085] The negative electrode active material layer of this application contains more than 20% natural graphite, which can better highlight the process effect and improve battery performance.
[0086] For example, the temperature of the roll forming process can be any two of the following values: 130℃, 140℃, 150℃, 160℃, 170℃. The linear pressure of the roll forming process can be any two of the following values: 115MPa, 120MPa, 130MPa, 140MPa, 150MPa, 160MPa, 170MPa. The belt conveyor speed can be any two of the following values: 6m / min, 7m / min, 8m / min, 9m / min.
[0087] After roll forming, the thickness of the negative electrode sheet is 150μm to 200μm. Negative electrode sheets with a thickness range of 150μm or 200μm can better meet the requirements of the roll forming process, balance the requirements of heat conduction, stress dispersion and negative electrode sheet forming, and obtain a negative electrode sheet with better performance.
[0088] For example, the thickness of the negative electrode sheet after roll forming includes, but is not limited to, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, 200μm, or any combination thereof.
[0089] A second aspect of this application provides a battery pack comprising a plurality of batteries connected in series, parallel, or mixed configurations, the batteries including those of the first aspect.
[0090] The battery pack of this application may consist of two or more batteries of the first aspect connected in series, parallel or mixed connection, wherein the connection method may be one or more of ultrasonic welding, resistance welding and laser welding.
[0091] Because the battery pack of this application includes the aforementioned battery, it also has advantages such as long cycle performance and high energy density.
[0092] A third aspect of this application provides an electrical device, including the battery of the first aspect or the battery pack of the second aspect.
[0093] This application does not limit the specific type of electrical equipment, and may include any device that requires battery power, such as electric vehicles, mobile phones, smart home devices, robots, drones, e-cigarettes, and speakers.
[0094] The electrical equipment provided in this application includes the aforementioned battery or battery pack, and therefore has good electrochemical performance and stability.
[0095] The negative electrode sheet provided in this application will be described in detail below through specific embodiments.
[0096] Unless otherwise specified, the reagents, materials and instruments used in the following examples are all conventional reagents, materials and instruments in the art, and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0097] Example 1
[0098] The method for preparing the negative electrode sheet provided in this embodiment includes the following steps:
[0099] 1. Preparation of negative electrode sheet: Mix negative electrode active material (100wt% natural graphite), conductive agent carbon black, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) in a mass ratio of 95.4:0.9:1.5:2.2, add deionized water, and stir in a vacuum mixer until a uniform slurry is formed; coat the negative electrode slurry onto the negative electrode current collector copper foil, and bake in an oven at 100℃ until dry.
[0100] 2. Negative electrode rolling: The dried negative electrode sheet is hot rolled at a rolling temperature of 140℃, a rolling linear pressure of 115MPa, and a belt speed of 8m / min. After slitting, the negative electrode sheet is obtained. The D50 of natural graphite is approximately 15μm, and the thickness of the prepared negative electrode sheet is 180μm.
[0101] 3. Positive Electrode Preparation: NCM811, a ternary material with a Dv50 of 6.5 μm, was used as the positive electrode active material. This active material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 96:2:2. N-methylpyrrolidone (NMP) solvent was added, and the mixture was stirred into a uniform slurry under vacuum. The positive electrode slurry was sieved (through a 200-mesh screen) and uniformly coated onto the positive electrode current collector aluminum foil. After drying in an oven at 120°C, it was rolled and slit to obtain a compacted density of 3.4 g / cm³. 3 The positive electrode plate.
[0102] 4. Electrolyte preparation: Ethyl carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then dry lithium salt LiPF6 is added to dissolve in the mixed solvent to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.
[0103] 5. Diaphragm preparation: Polyethylene film is selected as the diaphragm and cut into diaphragm sheets.
[0104] 6. Preparation of lithium-ion batteries: The positive electrode sheet, separator sheet and negative electrode sheet provided in all embodiments and comparative examples are stacked in sequence. The separator sheet must completely isolate the positive electrode sheet and the negative electrode sheet. Then, the stacked positive electrode sheet, separator sheet and negative electrode sheet are put into an aluminum-plastic film soft package, electrolyte is injected, and after vacuum sealing, standing, formation, cutting and sealing and other processes, a lithium-ion battery is obtained.
[0105] Example 2
[0106] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 1, except that: the negative electrode active material is composed of 30wt% natural graphite and 70wt% artificial graphite; the rolling pressure during the negative electrode rolling process is 130MPa and the belt speed is 7m / min.
[0107] Example 3
[0108] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 1, except that: the negative electrode active material is composed of 50wt% natural graphite and 50wt% artificial graphite; the rolling temperature during the negative electrode rolling process is 150℃, the rolling pressure is 150MPa, and the belt speed is 7m / min.
[0109] Example 4
[0110] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 1, except that the rolling temperature during the negative electrode rolling process is 140℃, the rolling pressure is 140MPa, and the belt speed is 8m / min.
[0111] Example 5
[0112] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 1, except that the rolling temperature during the negative electrode rolling process is 150℃, the rolling pressure is 150MPa, and the belt speed is 6m / min.
[0113] Example 6
[0114] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 1, except that the rolling temperature during the negative electrode rolling process is 130℃, the rolling pressure is 150MPa, and the belt speed is 9m / min.
[0115] Example 7
[0116] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 1, except that: the negative electrode active material is composed of 40wt% natural graphite and 60wt% artificial graphite; the rolling temperature during the negative electrode rolling process is 120℃, the rolling pressure is 120MPa, and the belt speed is 6m / min.
[0117] Comparative Example 1
[0118] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the negative electrode active material is composed of 20wt% natural graphite and 80wt% artificial graphite; the rolling temperature during the negative electrode rolling process is 110℃, the rolling pressure is 110MPa, and the belt speed is 8m / min.
[0119] Comparative Example 2
[0120] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the rolling temperature is 110℃, the rolling line pressure is 140MPa, the belt speed is 10m / min, and the negative electrode sheet is obtained after slitting.
[0121] Comparative Example 3
[0122] The preparation method of the negative electrode sheet in this comparative example is basically the same as that in Example 1, except that: lithium iron phosphate with a Dv50 of 1 μm is used as the positive electrode active material; specifically, the positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) solvent is added. The mixture is stirred into a uniform slurry under vacuum stirring. The positive electrode slurry is sieved (through a 200-mesh sieve) and uniformly coated onto the positive electrode current collector aluminum foil. After drying in an oven at 120°C, it is rolled and slit to obtain a compacted density of 2.7 g / cm³. 3 The positive electrode plate.
[0123] Test case
[0124] 1. XRD (C 101 +C 002 )test
[0125] The negative electrode sheets provided in all embodiments and comparative examples were used as samples, and the samples were tested respectively, including the following steps:
[0126] 1) Lay the negative electrode flat on the sample plate and perform XRD tests in an X-ray diffractometer to obtain the XRD spectrum. Record the wavelength λ (in nm) of the cathode rays used in the XRD test. The XRD test conditions are as follows: use copper Kα rays as the cathode rays, use 40kV and 20mA to excite the cathode ray source to generate X-rays, the test scan speed is 5° / min, and use a Kβ filter to remove the influence of Kβ rays on the peak shape and position of the spectrum.
[0127] 2) From the obtained XRD pattern of the negative electrode, obtain the diffraction angle 2θ (in °) of the diffraction peaks corresponding to the (101) and (002) crystal planes, and the half-width at half-peak (i.e., the diffraction angle corresponding to 1 / 2 peak height, in radians) of these two diffraction peaks. Then, calculate C according to Equations 2 and 3. 101 With C 002 Value, and calculate C 101 +C 002 It should be noted that the full width at half maximum (FWHM) of a diffraction peak on a specific crystal plane directly read from an XRD pattern is measured in degrees (°). When calculating the value of parameter K, the FWHM value in degrees needs to be converted to a value in radians.
[0128] 2. Pore density test
[0129] The pore size distribution of the negative electrode sheets provided in all embodiments and comparative examples was determined by mercury intrusion porosimetry in GB / T 21650.1-2008 / ISO 15901-1. The pore size distribution curves of the negative electrode sheets tested by mercury intrusion porosimetry were extracted, and the pore density of natural graphite was obtained by integrating the pore size distribution curves in the pore size range of 5 nm to 500 nm.
[0130] 3. Negative electrode compaction density test
[0131] The compaction density test method for the negative electrode sheet can be as follows: cut the negative electrode sheet into small circular pieces of a certain size, measure the weight of the negative electrode dressing in the small circular piece per unit area, calculate the areal density, and measure the thickness of the negative electrode dressing. The compaction density is obtained by calculating the areal density of the negative electrode sheet / (electrode sheet thickness - current collector thickness).
[0132] The test results for the above parameters are shown in Tables 1A and 1B, and C is calculated for all embodiments and comparative examples. 101 C 002 C 101 +C 002 ρ p Substituting PDa into Equation 1, the K values of the negative electrode sheets provided in all embodiments and comparative examples were calculated. Specific results are shown in Tables 1A and 1B.
[0133] Table 1A
[0134]
[0135]
[0136] Table 1B
[0137]
[0138] 4. Lithium-ion battery preparation and testing
[0139] (1) Energy density test:
[0140] Weigh the battery at 25℃. Under the same conditions, charge and discharge the prepared lithium-ion battery at a 1C rate, with a charging / discharging voltage range of 2.0V to 4.1V. Record the actual discharge amount. The ratio of the battery's actual 1C discharge energy to the volume of the negative electrode is the battery's volumetric energy density. See Table 2 for the specific results.
[0141] (2) Storage performance test:
[0142] The prepared lithium-ion battery was charged and discharged at a rate of 0.5C at 25℃, with a charge / discharge voltage range of 2.0V to 4.1V. The actual discharge amount recorded at this time is the nominal capacity. The lithium-ion battery was then charged to the cutoff voltage at a rate of 1C, with a charge / discharge voltage range of 2.0V to 3.8V. The lithium-ion battery was stored in a 25℃ constant temperature chamber for 28 days. At 25℃, the lithium-ion battery was discharged at a rate of 1C, and the actual discharge amount recorded at this time is the capacity after storage. The 28-day cycle retention rate is calculated as the capacity after storage divided by the nominal capacity, expressed as a percentage (%). Specific results are shown in Table 2.
[0143] (3) Cyclic performance test:
[0144] The prepared lithium-ion battery was charged and discharged at a rate of 0.5C at 25℃, with a charge-discharge voltage range of 2.0V to 4.1V. Full charge-discharge cycle tests were conducted until the capacity of the lithium-ion battery decayed to 80% of its initial capacity. The number of cycles was recorded. The specific results are shown in Table 2.
[0145] (4) Negative electrode expansion rate test:
[0146] The battery, after undergoing 10 cycles of room temperature cycling performance testing, was discharged to 0% SOC and disassembled in a glove box. The negative electrode was removed, and its thickness was measured using a micrometer. The change in this thickness compared to the electrode thickness after capacity testing was recorded as the electrode expansion rate after 10 cycles. The specific results are shown in Table 2.
[0147] Table 2
[0148]
[0149]
[0150] By combining Tables 1A, 1B, and 2, the following conclusions can be drawn:
[0151] By comparing the parameters of the negative electrode sheets in Examples 1-7 and Comparative Examples 1-2, and the battery data, it can be seen that when the K value of the negative electrode sheet is in the range of 6 to 18, and the positive electrode sheet includes lithium-containing layered metal oxide, the battery has both high energy density, cycle capacity retention rate, and low electrode expansion. However, the positive electrode sheet in Comparative Example 3 does not include lithium-containing metal oxide, and even if the K value of the negative electrode sheet is in the range of 6 to 18, the battery's energy density, storage capacity retention rate, and cycle capacity retention rate are relatively low, and the electrode expansion rate is relatively high.
[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A battery, characterized in that, It includes a negative electrode and a positive electrode, wherein the negative electrode and the positive electrode are stacked together; The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, which includes a carbon-based material, and the carbon-based material includes natural graphite. The negative electrode sheet satisfies K, where K is 6 to 18. Wherein, K is calculated using Equation 1: K = (C 101 +C 002 )×PDa×ρ P Formula 1; In Equation 1, C 101 and C 002 The crystallographic parameters of the carbon-based material are calculated using Equations 2 and 3, respectively, with units of nm; PDa is the compaction density of the negative electrode sheet, with units of g / cm³. 3 ;ρ P The pore density of the natural graphite in the negative electrode sheet is expressed in mL / g. C 101 =1.84×λ / (FWHM) 101 ×cosθ 101 Formula 2; C 002 =0.89×λ / (FWHM) 002 ×cosθ 002 Formula 3; In Equations 2 and 3, FWHM 101 and FWHM 002 θ represents the half-width at half-maximum (FWHM) of the (101) peak and the (002) peak in the X-ray diffraction pattern of the negative electrode, respectively, in radians; 101 and θ 002 λ represents half the 2θ values of the (101) peak and (002) peak in the X-ray diffraction pattern of the negative electrode, respectively, both in °; λ is the wavelength of the cathode ray used in X-ray diffraction, in nm. The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side surface of the positive current collector. The positive active material layer includes a positive active material, which includes a lithium-containing layered metal oxide.
2. The battery according to claim 1, characterized in that, C 101 +C 002 The wavelength range is 70nm to 120nm.
3. The battery according to claim 1 or 2, characterized in that, ρ P The concentration is 0.05–0.09 mL / g.
4. The battery according to any one of claims 1-3, characterized in that, PDa is 1.6–1.85 g / cm³. 3 .
5. The battery according to any one of claims 1-4, characterized in that, Based on the total mass of the negative electrode active material, the mass content of the natural graphite is 50% to 100%.
6. The battery according to any one of claims 1-5, characterized in that, The Dv50 of the natural graphite is 12μm to 18μm.
7. The battery according to any one of claims 1-6, characterized in that, The lithium-containing layered metal oxide includes one or more combinations of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, and nickel-cobalt-aluminum ternary materials.
8. The battery according to any one of claims 1-7, characterized in that, The compaction density PDc of the positive electrode is 3.2–3.6 g / cm³. 3 .
9. The battery according to any one of claims 1-8, characterized in that, Based on the total mass of the positive electrode active material, the mass content of the lithium-containing layered metal oxide is 60% to 98%.
10. The battery according to any one of claims 1-9, characterized in that, The Dv50 of the lithium-containing layered metal oxide is 5 μm to 12 μm.
11. A battery pack comprising a plurality of batteries connected in series, parallel, or mixed connections, characterized in that, The battery includes the battery of claim 10.
12. An electrical appliance, characterized in that, Includes the battery of claim 10 or the battery pack of claim 11.
